LEMBAGA WAKAF: SUATU SOLUSI PEMBIAYAAN PENDIDIKAN ISLAM - Muhayat, Imam (Sekolah Tinggi Agama Islam Muhammadiyah Tulungagung, 2013)
Fiqih reconstruktion is rebuilding new concept of fiqih (laws) that is egalitarian and fair. And the fiqh (Islamic laws) is meant to be the containing bias like fiqih, ibadah, muamalah, munakahah, jinayah, siyasah, waratsah and the new fiqih, fiqih biÃ¢â¬â¢ah.